Nano-engineered hydrocolloid-based delivery systems for natural flavonoids: From structural diversity to bioavailability enhancement and therapeutic applications - Yueming Wang; Amin Zhang; Wenjie Chu; Chengliang Qi; Tianxing Zhou; Yu Pan; Yuhan Wang; Chengyang Wang; Yuan Liu; Wenli Wang (Food Hydrocolloids, 2027)

Snorkel-biochar coupling enhances organic matter and nitrogen pollutant removal while mitigating greenhouse gas emissions through spatial redox regulation in bioretention systems - Ruohan Li; Wenying Sun; Yuepeng Deng; Hengxin Liu; Mingyue Yang; Yueming Han; Lixun Zhang (Water Research, 2026)

Involvement of NAC083-RbohD module in melatonin-delayed endocarp browning of longan fruit - Shuting Zhang; Jiaqi Xiao; Yueming Jiang (Postharvest Biology and Technology, 2026)

Spatial confinement in zeolites dominates pentene monomolecular cracking pathway - Fang Li; Weiyong Zhong; Min Sun; Yiran Wang; Penghe Zhang; Yueming Liu; Mingyuan He (Chemical Engineering Journal, 2026)

Mg/Fe-layered double hydroxide-loaded biochar enhances nitrogen retention and reduces geochemically reactive metal concentrations in paddy soil: Bacterial community responses - Hengxin Liu; Ruohan Li; Yueming Han; Yuntao Guan; Lixun Zhang (Process Safety and Environmental Protection, 2026)

MaHPCA1 alleviates chilling injury in banana fruit - Yu Hou; Peipei Fan; Xiangbin Xu; Zhengke Zhang; Yonggui Pan; Lanhuan Meng; Lisha Zhu; Haiming Chen; Jianbo Xiao; Yueming Jiang; Jiali Yang (Postharvest Biology and Technology, 2026)

FreqChange: Frequency-aware spatiotemporal learning with prior guidance for semantic change detection in remote sensing images - Haiyan Huang; Zhenfeng Shao; Duowang Zhu; Xiao Huang; Ruiqian Zhang; Qimin Cheng; Jindou Zhang; Yueming Duan; Deren Li (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

High magnetic field-driven assembly of collagen peptide-cerium chelates from fish skin: Microstructure, colloidal stability and absorption behavior - Peihan Wu; Hui Wang; Yueming Hu; Pingwei Wen; Liang Zhang; Peng Zhang; Xiaomei Sha; Zongcai Tu (Food Hydrocolloids, 2026)

Reactive heavy metals govern soil microbial communities: Depth-resolved evidence and disentangled metal-specific effects - Lixue Qiu; Chenle Wang; Fuxing Wu; Yueming Han; Lixun Zhang (Journal of Hazardous Materials, 2026)

Correction to: Life Cycle and Circadian Rhythms in Central Resident Immunity and Neuropsychiatric Pathology - Zhixin Lim; Ha Linh Nguyen; Yuanyuan Zeng; Qingyue Qu; Yan Le; Ming Sun; Xiaoyu Wang; Hong Zhu; Yuchen Qian; Saboor Saeed; Huaizhi Wang; Dazhong Rong; et al. (Neuroscience Bulletin, 2026)

Estimating downward shortwave radiation incorporating topographic effects using a hybrid physical and data-driven method: Algorithm development and long-term global product generation - Yichuan Ma; Tao He; Shunlin Liang; Xiaotong Zhang; Tim R. McVicar; Dejun Cai; Wanshan Peng; Yueming Zheng; Tong Liu; Xinyan Liu (Remote Sensing of Environment, 2026)

Effects of volcanic altitudes on the rhizosphere microbial community composition and structure of Euphorbia maculata - Yaozhou Zhang; Han Lin; Qixiu Cheng; Haining Wang; Yiming Zhang; Yueming Bao; Rui Qin; Xiaoyu Li; Jin Chen (Physiological and Molecular Plant Pathology, 2026)

Life Cycle and Circadian Rhythms in Central Resident Immunity and Neuropsychiatric Pathology - Zhixin Lim; Ha Linh Nguyen; Yuanyuan Zeng; Qigngyue Qu; Yan Le; Ming Sun; Xiaoyu Wang; Hong Zhu; Yuchen Qian; Saboor Saeed; Huaizhi Wang; Dazhong Rong; et al. (Neuroscience Bulletin, 2026)

Torque teno virus in the lower respiratory tract: association with immunosuppression but not mortality in severe pneumonia—a multicenter retrospective cohort study - Xian Zhang; Lifei Chen; Fang Wang; Xiaofang Xu; Yueming Wu; JunLong Xu; Yongan Xu; Xuwei He (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

Highly amphiphilicity-tailorable pineapple-like janus nanozymes with superior kinematic locomotion facilitates biphasic chemiluminescence analysis - Xin Jiang; Wan Wei; Yueming Zhao; Lingli Zhang; Wenwen Wang; Yuting Zhao; Zhongjie Zhu; Zhifeng Fu; Chengzhou Zhu; Hui Ouyang (Analytica Chimica Acta, 2026)

Transforming from ‘natural tools’ into ‘custom sensors’: combining directionally designed biological nanopore electrochemistry sensing lumens with AI-driven analytics to pioneer a new paradigm for food analysis - Yanyang Yu; Yongfei Deng; Zhiyong Cui; Yueming Wang; Chenxi Zhang; Jinna Wang; Danni Zhang; Tianxing Zhou; Chuyue Gong; Shengli Zhang (Trends in Food Science & Technology, 2026)

High-throughput characterization of local structural imperfections in freestanding oxide membranes by lock-in thermography - Ao Wang; Jinfeng Zhang; Jinxiang Yan; Fang Xu; Qing Wang; Yueming Huang; Minghui Fan; Qiming Lv; Zhengguo Liang; Kunjie Dai; Dazhi Hou; Wenbin Wu; et al. (Science Bulletin, 2026)

Dynamic patterns of constraints, drivers and impacts of land-based aquaculture areas and their implications: A case of Guangdong, China from 1990 to 2020 - Ku Gao; Xiaomei Yang; Zhihua Wang; Yueming Liu; Feilin Lai; Junyao Zhang (Land Use Policy, 2026)

Sense, think, and robot control: Multimodal material recognition sensing integrated with large language model reasoning - Zuowei Wang; Fuzheng Zhang; Qijing Lin; Yueming Gao; Bin Sun; Hongze Ke; Na Liu; Bian Tian; Libo Zhao; Zhuangde Jiang (Chemical Engineering Journal, 2026)

In-situ constructed Ag/CNT hierarchical networks in TPU nanofibers for dual-mode triboelectric sensing - Shiqiang Ouyang; Feijie Wang; Yichi Liu; Suyang Wang; Yaoli Wang; Yuefan Liu; Zhixuan Mei; Kaixin Liao; Shenzhuo Zhang; Yueming Hu; Shufeng Ma; Liqiang Wang (Chemical Engineering Journal, 2026)

Charge transfer and control mechanisms in contact-electron-activated artificial synapse - Xinke Yu; Xiongxin Luo; Gaosi Han; Yueming Zhang; Zhong Lin Wang; Laipan Zhu (Chemical Engineering Journal, 2026)

Alpha-ketoglutarate alleviates chilling injury in banana fruit by promoting redox homeostasis and maintaining energy balance - Yuemin Yang; Rufang Deng; Yueming Jiang; Xuewu Duan; Zhengke Zhang; Guoxiang Jiang; Mengting Liu (Postharvest Biology and Technology, 2026)

Piperlongumine Inhibits Malignant Progression of Esophageal Squamous Cells Through the PI3K/AKT Signaling Pathway - Jun Wang; Yueming Chu; Guangbing Hu; Shiqi Liang; Yutong Cui; Ji Zuo; Zichen Luo; Xinrui Chen; Xiaobo Wang; Zhenghang Yu; Zhongyang Zhang; Xianfei Wang (Biochemical Genetics, 2026)

Single-cell dissection of pleural and systemic immunity uncovers pathogen-specific immune reprogramming in tuberculosis versus lung adenocarcinoma - Sifei Yu; Yueming Liang; Jing Chen; Beiying Zhang; Chuling Zhang; Yuwen Zhao; Rong Yan; Yichu Nie; Xiaofan Mao (Inflammation Research, 2026)

Physicochemical properties of edible oxidized gum arabic–polylysine crosslinked films and their effects on the postharvest preservation of litchi - Dan Li; Huirong Cheng; Ling Xie; Hong Luo; Dandan Zhang; Jupeng Zhao; Yueming Jiang; Liang Gong (Postharvest Biology and Technology, 2026)

Corrigendum to “Insight on the interaction between chickpea protein isolate and dextran: Structural analysis, functional characterization and co-encapsulated W/O/W emulsion formation” [Food Res. Int. 213 (2025) 116593] - Jing Zhang; Yan Shi; Yueming Hu; Wei Fan; Wei Liu; Yipu Liu (Food Research International, 2026)

Ecological drivers of multidimensional temporal beta diversity of phytoplankton communities in a temperate lake over 20 years - Xiaoguang Zhang; Yueming Qu; Qinghua Cai; Lin Ye (Aquatic Ecology, 2026)

Application of riboflavin delays the browning of harvested litchi during storage at room temperature - Jiechun Peng; Ting Li; Mengting Liu; Jiangtao Zhang; Xiaoyan Duan; Ying Li; Hanzhi Liang; Pedro Garcia-Caparros; Yueming Jiang; Xuewu Duan (Food Control, 2026)

Bromide-containing surfactants enabling singlet oxygen-dominated non-radical oxidation process for efficient degradation of aromatic pollutants in soil and groundwater - Yueming Han; Zhuolun Li; Guanqing Chen; Hengxin Liu; Shichao Feng; Yuntao Guan; Lixun Zhang (Process Safety and Environmental Protection, 2026)

Apyrase MaAPY2 regulates the chilling tolerance of banana fruit as a negative modulator - Ying Li; Wanqi Chen; Shule Chen; Zhuojia Mao; Shihan Huang; Rufang Deng; Dandan Zhang; Taotao Li; Xuewu Duan; Yueming Jiang (Postharvest Biology and Technology, 2026)

Analytical solution for transient groundwater flow to partially penetrated waterproof curtains in unconfined aquifers - Qian Wang; Jiangwei Zhang; Enze Ma; Yueming Qi; Liyang Xu; Yue Fan; Xiuyu Liang (Journal of Hydrology, 2026)

Mitigating methane emissions from municipal solid waste in Chinese cities - Yueming Gao; Yang Duan; Wei Zhang; Nana Zhao; Yuan Wang; Zhenyu Ding; Wenjun Wu; Dong Cao; Hongqiang Jiang (Journal of Environmental Management, 2026)

Activating V4+/V5+ redox couple in polyanion lattice engineered Na3.1V2(PO4)2.9(SiO4)0.1-CNT by synergistic ionotronic strategy - Anyang Yu; Qi Fan; Zilong Fang; Tian Jiang; Xinxin Wang; Xiedie Zhao; Xiaoshuang Ma; Pingping Sun; Gang Li; Shijun Yuan; Haiyang Zhang; Yining Wang; et al. (Chemical Engineering Journal, 2025)

Physiological and Metabolomic Analysis in Roots of Hordeum jubatum L. In Response to Iso-osmotic Stress - Peilin Han; Xiaolin Di; Bing Gao; Jinji Han; Yueming Li; Xiaoxia Deng; Zhuoran Tan; Jingnan Zhang; Jinghong Wang (Journal of Soil Science and Plant Nutrition, 2025)

Pore structure modulation and surface functionalization boosted adsorption of PFAS on porous carbon: Experimental and theoretical investigations - Bei Zhang; Daiki Moriyama; Thilini Maheshika Herath; Huan Zhao; Yuqiao Bai; Yueming Dang; Wei Liu; Hiromichi Kato; Koichi Yamamoto; Yasuhide Mochizuki; Naoki Arimitsu; Akira Nakajima; et al. (Journal of Hazardous Materials, 2025)

Molecular mechanisms of superheated steam-induced modifications enhancing ovalbumin functional properties: Insights from site identification and peptidomic analysis - Haiqi Chen; Zuohua Xie; Feifei Wang; Zongcai Tu; Pingwei Wen; Siqiong Zhang; Hui Wang; Yueming Hu (Food Chemistry, 2025)

Umami_IP: An integrated model and explanatory analysis for quantitative prediction of Umami recognition threshold - Zhiyong Cui; Yueming Wang; Tianxing Zhou; Jiaming Gu; Zhiwei Zhang; Wenli Wang; Yuan Liu (Food Chemistry, 2025)

Enhancing the output of cellulose-based triboelectric nanogenerators via dual interfacial polarization effects - Feijie Wang; Suyang Wang; Hao Wang; Yichi Liu; Shiqiang Ouyang; Shenzhuo Zhang; Yueming Hu; Junhua Zhao; Shufeng Ma; Zhen Wu; Liqiang Wang (Carbohydrate Polymers, 2025)

Small-mammalian fossils from the Paleolithic Dayin Cave site in Yunnan, Southwest China - Yinan Zhang; Feng Gao; Yang Wan; Fan Yang; Bin Gao; Yueming Zeng; Bo Liu; Zetao Zhang; Wenwei Huang; Weiming Wang; Qiang Li; Xijun Ni (Quaternary International, 2025)

MOFs-derived FeNi bimetallic phosphide with tightly coupled heterogeneous interface for PMS activation - Xiaoyang Liu; Yueming Zhu; Minghui He; Chenyu Zhang; Gancheng Zuo; Yuting Wang; Shaogui Yang; Huan He (Chemical Engineering Journal, 2025)

ALN-modified MnO2-x/PEEK implant for bone-targeted catalytic therapy in postoperative osteosarcoma repair - Miaomiao He; Ce Zhu; Dan Sun; Yueming Song; Ganjun Feng; Limin Liu; Li Zhang (Chemical Engineering Journal, 2025)

Gene flow network of four major pigments and role of LcmiR2111-KFB14 in pericarp browning of litchi during storage - Jiaqi Xiao; Shuting Zhang; Yijie Zhou; Xiangjin Kong; Hong Zhu; Yueming Jiang; Hongxia Qu (Postharvest Biology and Technology, 2025)

In vivo cell migratory behavior drives therapeutic efficacy evidenced by SWIR fluorescence imaging - Huizhu Li; Xiao Zhang; Shunyao Li; Yueming Wang; Shingo Ogura; Kemeng Shao; Xiner Du; Yan Wo; Shiyi Chen; Jun Chen; Xuanfeng Qin; Yunxia Li; et al. (Chemical Engineering Journal, 2025)

Homoeologous recombination-based transfer and cytological mapping of the novel powdery mildew resistance gene Pm7C from Aegilops caudata - Yueming Ren; Mengzhen Luo; Yajun Feng; Qifan Chen; Chao Ma; Wenxuan Liu; Fu Guo; Qianwen Liu; Muhammad Amjad; Ranran Jia; Xinpei He; Xiang Ji; et al. (Theoretical and Applied Genetics, 2025)

Simulated Study of a Multi-stage Permeable Reactive Barrier for In-Situ AMD Treatment of a Closed High-Sulfur Coal Mine - Yueming Qi; Pei Zhou; Dan Jiang; Lai Zhou; Yanzhuo Liu; Jiehui Zhang (Mine Water and the Environment, 2025)

Insight on the interaction between chickpea protein isolate and dextran: Structural analysis, functional characterization and co-encapsulated W/O/W emulsion formation - Jing Zhang; Yan Shi; Yueming Hu; Wei Fan; Wei Liu; Yipu Liu (Food Research International, 2025)

Passive Synthetic Aperture for Direction-of-Arrival Estimation Using an Underwater Glider with a Single Hydrophone - Yueming Ma; Jie Sun; Shuo Li; Tianze Hu; Shilong Li; Yuexing Zhang (Journal of Marine Science and Engineering, 2025)
This paper addresses the aperture limitation problem faced by array-equipped underwater gliders (UGs) in direction-of-arrival (DOA) estimation. A passive synthetic aperture (PSA) method for DOA estimation using a single hydrophone mounted on a UG is proposed. This method uses the motion of the UG to synthesize a linear array whose elements are positioned to acquire the target signal, thereby increasing the array aperture. The dead-reckoning method is used to determine the underwater trajectory of the UG, and the UG’s trajectory was corrected by the UG motion parameters, from which the array shape was adjusted accordingly and the position of the array elements was corrected. Additionally, array distortion caused by movement offsets due to ocean currents underwent linearization, reducing computational complexity. To validate the proposed method, a sea trial was conducted in the South China Sea using the Haiyi 1000 UG equipped with a hydrophone, and its effectiveness was demonstrated through the processing of the collected data. The performance of DOA estimation prior to and following UG trajectory correction was compared to evaluate the impact of ocean currents on target DOA estimation accuracy.

Synergistic impact of plant essential oil based microemulsion on lychee preservation in comparison to Prochloraz - Yujie Shen; Xin Zhou; Jupeng Zhao; Zhe Wang; Dandan Zhang; Lingrong Wen; Yueming Jiang; Liang Gong (Sustainable Chemistry and Pharmacy, 2025)

Characterization of two novel angiotensin converting enzyme-inhibitory peptides from yellow tuna peptides: Inhibitory mechanism, transport route and network pharmacology analysis - Jinxin Wang; Si-jie Guo; Xing Xie; Tian-xin Ma; Qin-hui Wen; Yong-lin Gao; Yueming Li; Jian Zhang; Wenjun Li; Lu Zhang (Food Research International, 2025)

Construction of W/O/W microcapsules based on the combination of polyglycerol polyricinoleate/protein for the co-encapsulation of crocin and quercetin: Physical properties, stability and in vitro digestion - Wei Fan; Yan Shi; Yueming Hu; Shu Wang; Jing Zhang; Wei Liu (Food Chemistry, 2025)

Transcription factor AcAGL9 and AcBEH1 synergistically regulate carotenoid biosynthesis during pineapple fruit ripening - Mengting Liu; Ting Li; Rufang Deng; Zhengke Zhang; Yijie Zhou; Xuewu Duan; Yueming Jiang; Guoxiang Jiang (Postharvest Biology and Technology, 2025)

Evaluation of factors influencing full wave equation depth migration - Anyu Li; Yueming Ye; Xiangyu Zhu; Tao Liu; Huimin Zhang; Yong Xia (Journal of Applied Geophysics, 2025)

Mapping of Rsn2, a locus conferring rice tolerance to toxin from the causal agent of rice sheath blight Rhizoctonia solani - Xiang Xue; Yu Wang; Yueming Xu; Yumei Zhang; Fang Gu; Yuyin Ma; Zongxiang Chen; Yafang Zhang (Journal of Plant Pathology, 2025)

Mitigating particulate matter dispersion from urban earthen sites: A case study of city walls in Zhengzhou, China - Yueming Wen; Yu Miao; Renjing Zhao; Yaowen Shi; Jiangxing Miao; Chang Lv; Guang Zhang (Sustainable Cities and Society, 2025)

Freezing or searing: Unraveling the impact of extreme temperatures on poverty in China - Huiming Zhang; Shuyuan Wang; Kai Wu; Yueming (Lucy) Qiu; Shouyang Wang; Yongfan Zhao (Environmental Impact Assessment Review, 2025)

Porous spherical g-C3N4/geopolymer composite for photo-Fenton-like degradation of tetracycline hydrochloride - Yutong Song; Xiaohong Zhang; Chengying Bai; Wei Peng; Yueming Ren; Xiaodong Wang; Ting Zheng; Paolo Colombo; Bin Wang (Journal of Water Process Engineering, 2025)

Mechanism studies of gliadin-glucose glycation reaction and products formation by heat treatment with different conduction modes - Qiannan Jiang; Xiangfei Hu; Zongcai Tu; Pingwei Wen; Yueming Hu; Siqiong Zhang; Hui Wang; Zuohua Xie (Food Chemistry, 2025)

Understanding the anti-browning mechanism and physicochemical properties in potato pulp during the magnetic field processing - Jialin Song; Mingming Qi; Feng Han; Mei Xu; Yueming Li; Xin Zhang; Chuangshuo Yan; Yujian Xie; Dongliang Zhang; Hongjun Li (Food Chemistry, 2025)

Exploring the influence of extruded rice adjunct on wort separation efficiency: A bio-macromolecule degradation perspective - Lijun Jiang; Jialin Song; Mingming Qi; Feng Han; Mei Xu; Yueming Li; Dongliang Zhang; Shifeng Yu; Hongjun Li (Food Chemistry, 2025)

Progress in Preparation Technology and Functional Research On Marine Bioactive Peptides - Jing Wang; Fengcheng Li; Wenjun Li; Yueming Li; Jian Zhang; Song Qin (Marine Biotechnology, 2025)

Gallic acid reduces pericarp browning of litchi fruit during storage - Chunlan Wang; Shuting Zhang; Dandan Zhang; Fengjun Li; Lihong Xie; Tingrui Dai; Yueming Jiang (Postharvest Biology and Technology, 2025)

Interaction of Ca2+ and Fe3+ in co-precipitation process induced by Virgibacillus dokdonensis and its application - Huaxiao Yan; Yuping Liu; Haojuan Zhang; Shengping Jin; Zuozhen Han; Jusun Woo; Maurice E. Tucker; Long Meng; Xiangqun Chi; Chao Han; Yanyang Zhao; Yueming Zhao; et al. (Journal of Environmental Sciences, 2025)

Improving the functional components and biological activities of navel orange juice through fermentation with an autochthonous strain Lactiplantibacillus paraplantarum M23 - Meiling Huang; Chunling Lai; Yan Liang; Qin Xiong; Chaoyun Chen; Zhiran Ju; Yueming Jiang; Jun Zhang (Food and Bioproducts Processing, 2025)

Multifunctional neuroimmunoregulatory nanoenzyme-enhanced hydrogel promotes bone regeneration by improving bone healing microenvironment - Qiujiang Li; Xingxia Long; Linnan Wang; Xi Yang; Huiliang Yang; Bowen Hu; Ce Zhu; Zhuang Zhang; Zhipeng Deng; Junhu Li; Shuxin Zheng; Lei Wang; et al. (Chemical Engineering Journal, 2025)

Association between exposure to arsenic, cadmium, and lead and chronic kidney disease: evidence from four practical statistical models - Jiongli Huang; Jingying Mao; Huilin Liu; Zhongyou Li; Guiyun Liang; Dabiao Zhang; Junchao Yang; Wen Qin; Pingjing Wen; Yueming Jiang; Zhaoyu Mo (Environmental Geochemistry and Health, 2025)

An update of aurones: food resource, health benefit, biosynthesis and application - Jiali Yang; Zhengjiao Gao; Zhiqian Yu; Yu Hou; Dingtao Tang; Huiling Yan; Fuwang Wu; Sui Kiat Chang; Yonggui Pan; Yueming Jiang; Zhengke Zhang; Bao Yang (Critical Reviews in Food Science and Nutrition, 2024)

Development of an integrated online deposition and corrosion monitoring system in a full-scale solid waste CFB boiler - Yueming Wang; Jinghui He; Yuxing Wang; Feiyue Sun; Chenxi Lu; Shuo Zhang; Lunbo Duan (Waste Management, 2024)

Fermentation by Penicillium polonicum improves the functional components and biological effects of orange peel via producing β-glucosidase without the risk of potential mycotoxins - Yan Liang; Chunling Lai; Liangliang Gao; Qingna Wu; Meiling Huang; Yueming Jiang; Jun Zhang (Food Bioscience, 2024)

Review the antioxidant and angiotensin converting enzyme inhibitory peptides derived from fish: Preparation, structure-relationship, bioavailability and ameliorating strategies - Shu Wang; Lu Zhang; Hui Wang; Bizhen Zhong; Yueming Hu; Hongmei Yin; Zongcai Tu (Food Bioscience, 2024)

Magnetic field: A non-thermal technology in food processing - Shu Wang; Lu Zhang; Hui Wang; Wei Fan; Yueming Hu; Zongcai Tu (Food Control, 2024)

Fabrication of antimicrobial packaging based on polyaminopropyl biguanide incorporated pectin/polyvinyl alcohol films for fruit preservation - Mingyang He; Jinpeng Pan; Min Hong; Yujie Shen; Heng Zhang; Yueming Jiang; Liang Gong (Food Chemistry, 2024)

Tert-Butylhydroquinone retards longan fruit deterioration by regulating membrane lipid and energy metabolisms - Zhiqian Yu; Dingtao Tang; Zhengke Zhang; Yueming Jiang; Jiali Yang; Yonggui Pan (Food Chemistry, 2024)

Continuous-flow degradation of Orange I using CoFe2O4-loaded activated carbon catalyst: Optimization of reaction parameters and toxicity prediction - Meiqi Li; Yuan Zong; Jing Feng; Hexin Zhang; Chengying Bai; Yueming Ren (Chemical Engineering Journal, 2024)

Lithology and elevated temperature impact phoD-harboring bacteria on soil available P enhancing in subtropical forests - Fujing Pan; Qian Yang; Yueming Liang; Xuan Yu; Peilei Hu; Wei Zhang; Yuelan Pang (Science of The Total Environment, 2024)

Advances in gas fumigation technologies for postharvest fruit preservation - Wanli Zhang; Yonggui Pan; Yueming Jiang; Zhengke Zhang (Critical Reviews in Food Science and Nutrition, 2024)

Multi-rater Prism: Learning self-calibrated medical image segmentation from multiple raters - Junde Wu; Huihui Fang; Jiayuan Zhu; Yu Zhang; Xiang Li; Yuanpei Liu; Huiying Liu; Yueming Jin; Weimin Huang; Qi Liu; Cen Chen; Yanfei Liu; et al. (Science Bulletin, 2024)

Sodium selenite enhances the production of functional proteins and biomass in Chlorella pyrenoidosa 038F by promoting acetate assimilation under heterotrophic cultivation - Jingjing Shangguan; Na Yang; Litao Zhang; Jianguo Liu; Yueming Li; Jianchun Xu; Xiuluan Xia; Bingzheng Xu (Aquaculture, 2024)

Hydrogen peroxide receptors regulate chilling injury of banana fruit during low-temperature storage - Shuting Zhang; Youxia Shan; Ying Li; Junxian He; Yueming Jiang (Postharvest Biology and Technology, 2024)

The unequal impacts of extremely high temperatures on households’ adaptive behaviors: Empirical evidence from fine-grained electricity consumption data - Han Shi; Bo Wang; Yueming Lucy Qiu; Nana Deng; Baichen Xie; Bin Zhang; Shijun Ma (Energy Policy, 2024)

Pore shrinkage capacity of Shajiang black soils (Vertisols) on the North China Plain and its influencing factors - Yueming CHEN; Zhongbin ZHANG; Lei GAO; Zichun GUO; Peng XIONG; Fahui JIANG; Xinhua PENG (Pedosphere, 2024)

Improved hourly estimate of aerosol optical thickness over Asian land by fusing geostationary satellites Fengyun-4B and Himawari-9 - Yueming Cheng; Tie Dai; Daisuke Goto; Lin Chen; Yidan Si; Hiroshi Murakami; Mayumi Yoshida; Peng Zhang; Junji Cao; Teruyuki Nakajima; Guangyu Shi (Science of The Total Environment, 2024)

A new curve of critical leaf nitrogen concentration based on the maximum root dry matter for diagnosing nitrogen nutritional status of sweetpotato - Zhi Zhang; Ximing Xu; Minghuan Jin; Jiacheng Bai; Xing Shu; Lijuan Deng; Siyu Wang; Yueming Zhu; Yuheng Liu; Guoquan Lu; Zunfu Lv (European Journal of Agronomy, 2024)

Structural insight into the dual-antagonistic mechanism of AB928 on adenosine A2 receptors - Yuan Weng; Xinyu Yang; Qiansen Zhang; Ying Chen; Yueming Xu; Chenyu Zhu; Qiong Xie; Yonghui Wang; Huaiyu Yang; Mingyao Liu; Weiqiang Lu; Gaojie Song (Science China Life Sciences, 2024)

Evaluation of coastal zone development and utilization considering natural ontology, a case study in Liaoning Province, China - Guo Yu; Zhihua Wang; Yueming Liu; Xiaomei Yang; Junyao Zhang; Ku Gao (Ocean & Coastal Management, 2024)

Green and efficient approach to extract bioactive flavonoids with antioxidant, antibacterial, antiglycation, and enzyme inhibitory activities from navel orange peel - Chunling Lai; Meiling Huang; Qin Xiong; Yan Liang; Yueming Jiang; Jun Zhang (Sustainable Chemistry and Pharmacy, 2024)

Nitrogen-doped biochar/MnO2 as an efficient PMS activator for synergistic BPA degradation via non-free radical pathways in the water - Hang Chen; Xiao Li; Weizhuo Li; Jing Feng; Ying Zhao; Hexin Zhang; Yueming Ren (Journal of Environmental Chemical Engineering, 2024)

Efficient preparation of oyster hydrolysate with aroma and umami coexistence derived from ultrasonic pretreatment assisted enzymatic hydrolysis - Junwei Zhang; Zongcai Tu; Zizi Hu; Yueming Hu; Hui Wang (Food Chemistry, 2024)

Benzotrithiophene-based covalent organic frameworks as efficient catalysts for artificial photosynthesis of H2O2 in pure water - Mingjie Liu; Peipei He; Hantao Gong; Zhenghua Zhao; Yueming Li; Kai Zhou; Yuemin Lin; Jing Li; Zongbi Bao; Qiwei Yang; Yiwen Yang; Qilong Ren; et al. (Chemical Engineering Journal, 2024)

Wide pH photocatalytic nitrate reduction at adaptive microenvironment-dominated liquid–liquid-solid trilayer reaction interfaces - Xiao Li; Jin Chang; Hexin Zhang; Jing Feng; Jun Ma; Chengying Bai; Yueming Ren (Chemical Engineering Journal, 2024)

Control of citrus blue and green molds by Actinomycin X2 and its possible antifungal mechanism - Liangliang Gao; Yan Liang; Qin Xiong; Meiling Huang; Yueming Jiang; Jun Zhang (Pesticide Biochemistry and Physiology, 2024)

Enhanced photocarrier separation in Br substitution-induced [W(VI)O6−x] units for highly efficient photocatalytic nitrate reduction under alkaline conditions - Xiao Li; Jin Chang; Hexin Zhang; Jing Feng; Jun Ma; Chengying Bai; Yueming Ren (Journal of Hazardous Materials, 2024)

Liraglutide attenuates palmitate-induced apoptosis via PKA/β-catenin/Bcl-2/Bax pathway in MC3T3-E1 cells - Lanlan Cheng; Yijing Xu; Yueming Long; Fangmei Yu; Li Gui; Qiu Zhang; Yunxia Lu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Ubiquitin ligase enzymes and de-ubiquitinating enzymes regulate innate immunity in the TLR, NLR, RLR, and cGAS-STING pathways - Wang Jiang; Mengling Li; Siyuan Peng; Tian Hu; Yan Long; Jiayi Zhang; Dan Peng; Yueming Shen (Immunologic Research, 2023)

Changes in the spatial distribution of mariculture in China over the past 20 years - Yueming Liu; Zhihua Wang; Xiaomei Yang; Shaoqiang Wang; Xiaoliang Liu; Bin Liu; Junyao Zhang; Dan Meng; Kaimeng Ding; Ku Gao; Xiaowei Zeng; Yaxin Ding (Journal of Geographical Sciences, 2023)

Increased aerosol scattering contributes to the recent monsoon rainfall decrease over the Gangetic Plain - Tong Ying; Jing Li; Zhongjing Jiang; Guanyu Liu; Zhenyu Zhang; Lu Zhang; Yueming Dong; Chuanfeng Zhao (Science Bulletin, 2023)

Effects of different high-temperature conduction modes on the ovalbumin-glucose model: AGEs production and regulation of glycated ovalbumin on gut microbiota - Haiqi Chen; Yanru Zhou; Siqiong Zhang; Zuohua Xie; Pingwei Wen; Hui Wang; Yueming Hu; Peihan Wu; Jiaojiao Liu; Qiannan Jiang; Zongcai Tu (Food Research International, 2023)

Comparison of ovalbumin glycation induced by high-temperature steaming and high-temperature baking: A study combining conventional spectroscopy with high-resolution mass spectrometry - Yueming Hu; Haiqi Chen; Yifan Yang; Siqiong Zhang; Zuohua Xie; Jiaojiao Liu; Qiannan Jiang; Jun Liu; Pingwei Wen (Food Research International, 2023)

In-situ measuring and predicting dynamics of soil bulk density in a non-rigid soil as affected by tillage practices: Effects of soil subsidence and shrinkage - Yuekai Wang; Zhongbin Zhang; Zichun Guo; Yueming Chen; Junsheng Yang; Xinhua Peng (Soil and Tillage Research, 2023)

H2O2-activated transcription factor MdERF4 negatively regulates ethylene biosynthetic during fruit ripening by suppressing MdACS1 transcription - Nannan Zang; Xiaojing Li; Liyong Qi; Zhuoran Zhang; Yueming Yang; Zepeng Yin; Aide Wang (Postharvest Biology and Technology, 2023)

Revealing the crystal phase effect of CeO2 in spinel-based nanocatalysts toward the peroxymonosulfate activation for organics degradation - Yuxuan He; Yueming Zhu; Jin Qian; Peifang Wang; Yuhang Zhang; Kailin Xu; Bianhe Lu; Yin Liu; Junwei Shen (Chemical Engineering Journal, 2023)

Relationship between summer time near-surface ozone concentration and planetary boundary layer height in Beijing - Chongzhao Zhang; Zhongjing Jiang; Meijing Liu; Yueming Dong; Jing Li (Atmospheric Research, 2023)

Retrieval of aerosol single scattering albedo using joint satellite and surface visibility measurements - Yueming Dong; Jing Li; Xing Yan; Chong Li; Zhongjing Jiang; Changrui Xiong; Liang Chang; Lu Zhang; Tong Ying; Zhenyu Zhang (Remote Sensing of Environment, 2023)

Characterization of nongxiang- and soy sauce-type distilled grains and their application in enhancing polyunsaturated fatty acid and triacylglyceride production from Chlorella sp. 038F - Na Yang; Jingjing Shangguan; Litao Zhang; Yueming Li; Jianchun Xu; Xiuluan Xia; Jianguo Liu (Journal of Environmental Chemical Engineering, 2023)

Hypergolic ignition induced by head-on collision of bi-propellant droplets: Monoethanolamine-based fuel and hydrogen peroxide - Dawei Zhang; Dehai Yu; Yueming Yuan; Peng Zhang; Xuejun Fan (Fuel, 2023)

The roles of exogenous ATP in postharvest fruit and vegetable: A systematic meta-analysis - Youxia Shan; Shuting Zhang; Ying Li; Jun Zhang; Mohamed A. Farag; Jun-Xian He; Jianbo Xiao; Hongxia Qu; Xuewu Duan; Yueming Jiang (Postharvest Biology and Technology, 2023)

Linoleic acid from the endophytic fungus Diaporthe sp. HT-79 inhibits the growth of Xanthomonas citri subsp. citri by destructing the cell membrane and producing reactive oxygen species (ROS) - Huiting Lin; Yan Liang; Kumaravel Kaliaperumal; Qin Xiong; Shuo Duan; Yueming Jiang; Jun Zhang (Pesticide Biochemistry and Physiology, 2023)

Peroxymonosulfate activation by Ru/CeO2 for degradation of Triclosan: Efficacy, mechanisms and applicability in groundwater - Chaomeng Dai; Xueji You; Qian Liu; Yueming Han; Yanping Duan; Jiajun Hu; Jixiang Li; Zhi Li; Lang Zhou; Yalei Zhang; Shuguang Liu (Chemical Engineering Journal, 2023)

Amelioration of chilling injury in ‘Guifei’ mango fruit by melatonin is associated with regulation of lipid metabolic enzymes and remodeling of lipidome - Ping Xu; Donald J. Huber; Di Gong; Ze Yun; Yonggui Pan; Yueming Jiang; Zhengke Zhang (Postharvest Biology and Technology, 2023)

Electron-transfer pathways insights into contaminants oxidized by Cu-OOSO3- intermediate: Effects of oxidation states of Cu and solution pH values - Lele Zhao; Jiaming Zhang; Zhiping Zhang; Yujun Zhu; Yuan Zong; Chengying Bai; Tong Wei; Yueming Ren; Jun Ma (Journal of Hazardous Materials, 2023)

Novel insights into Co synergy and electron-transfer pathways during the oxidation of contaminants by Cu-OOSO3- in CuCo2Ox/peroxymonosulfate system - Lele Zhao; Jiaming Zhang; Yuan Zong; Jun Ma; Chengying Bai; Hexin Zhang; Yueming Ren (Journal of Environmental Chemical Engineering, 2023)

A novel N-arachidonoyl-l-alanine-catabolizing strain of Serratia marcescens for the bioremediation of Cd and Cr co-contamination - Xiaoyan Sun; Huiping Feng; Jialiang Luo; Li Lin; Haixiang Zhang; Yali Duan; Fan Liu; Kailu Zhang; Baijie Wang; Dong Li; Yueming Hu; Zhiqiang Zhu (Environmental Research, 2023)

Nitric oxide is involved in melatonin-induced cold tolerance in postharvest litchi fruit - Jialiang Liu; Wanli Zhang; Meijiao Hu; Yonggui Pan; Yueming Jiang; Zhengke Zhang; Guoxiang Jiang (Postharvest Biology and Technology, 2023)

Multiple metabolomics comparatively investigated the pulp breakdown of four dragon fruit cultivars during postharvest storage - Qixian Wu; Huijun Gao; Ziming You; Zhengke Zhang; Hong Zhu; Mingyang He; Junxian He; Xuewu Duan; Yueming Jiang; Ze Yun (Food Research International, 2023)

Study on structure-activity relationship (SAR) of simplified mirogabalin derivatives as voltage-gated calcium channel α2δ ligands for the treatment of chronic neuropathic pain - Yuanwen Zhang; Yueming Zheng; Qingqing Wu; Fuyun Tian; Chuanjun Ma; Haiyan Xu; Li Zhan; Zhaobing Gao; Guilong Zhao; Huihui Ti (Medicinal Chemistry Research, 2023)

Construction of a Diagnostic Model for Distinguishing Benign or Malignant Bone Cancer by Mining miRNA Expression Data - Yueming Zhang; Jianwei Hu; Tao Li; Shizhu Hao; Xiaotang Wu (Biochemical Genetics, 2023)

Decreasing Vulnerability of Storm Surge Disasters in Coastal Cities of China over the Past 30 Years - Dan Meng; Yueming Liu; Zhihua Wang; Xiaomei Yang; Xiaoliang Liu; Junyao Zhang; Ku Gao (Journal of Marine Science and Engineering, 2023)
From 2000 to 2020, storm surges occurred 397 times in China, resulting in direct economic losses of up to CNY 220.64 billion. Storm surges not only threaten safety but also cause property damage; hence, it is necessary to assess the changes in vulnerability to storm surges in order to understand how to reduce said vulnerability. Fifteen coastal cities of four types were chosen, with different levels of urban development, rapid expansion of impervious surface, high extent of agricultural land, and high fishery output value. Viewing vulnerability through the dimensions of exposure, sensitivity, and adaptability, a GIS and RS were used to evaluate and assess the vulnerability in 15 coastal cities in China over the past 30 years. The results indicated that the vulnerability of these 15 Chinese cities presented the characteristics of a continuous downward trend from 1990 to 2020, and the average rate of reduction in vulnerability over the 10 years from 2005 to 2015 was the highest, at 2.23%. The areas of high vulnerability shifted from the southern region to the northern region. The vulnerabilities in the southern region, with Shanghai, Shenzhen, and Dongguan, changed significantly, to 3.30%, 3.20%, and 3.45%, respectively. An important factor in determining vulnerability reductions is a city’s ability to adapt to storm surges. Coastal cities can improve their adaptability to storm surge disasters through general public budget expenditure, investment in fixed assets, GDP, and medical and health services, thereby alleviating their vulnerability. Due to China’s frequent storm surge disasters during the 2005–2015 period, government departments have strengthened the investment of relevant resources in adaptive indicators, ultimately causing the cities’ vulnerability to rapidly decrease during this period.

Integration of metabolomics and proteomics analysis to explore the mechanism of neurotoxicity induced by receipt of isoniazid and rifampicin in mice - Xiaoyu Qu; Jie Ma; Huan Gao; Yueming Zhang; Jinghui Zhai; Jiawei Gong; Yanqing Song; Tingting Hu (NeuroToxicology, 2023)

MiR-139-5p/ENAH Affects Progression of Hepatocellular Carcinoma Cells - Yueming Zhang; Meng Li; Yinghuan Qiu; Yuhua Wu; Shan Chen; Bin Ni; Ding Tang; Zhouzi Deng; Zhiqiang Hu (Biochemical Genetics, 2022)

Radiomics based on readout-segmented echo-planar imaging (RS-EPI) diffusion-weighted imaging (DWI) for prognostic risk stratification of patients with rectal cancer: a two-centre, machine learning study using the framework of predictive, preventive, and personalized medicine - Zonglin Liu; Yueming Wang; Fu Shen; Zhiyuan Zhang; Jing Gong; Caixia Fu; Changqing Shen; Rong Li; Guodong Jing; Sanjun Cai; Zhen Zhang; Yiqun Sun; et al. (EPMA Journal, 2022)
Background Currently, the rate of recurrence or metastasis (ROM) remains high in rectal cancer (RC) patients treated with the standard regimen. The potential of diffusion-weighted imaging (DWI) in predicting ROM risk has been reported, but the efficacy is insufficient. Aims This study investigated the potential of a new sequence called readout-segmented echo-planar imaging (RS-EPI) DWI in predicting the ROM risk of patients with RC using machine learning methods to achieve the principle of predictive, preventive, and personalized medicine (PPPM) application in RC treatment. Methods A total of 195 RC patients from two centres who directly received total mesorectal excision were retrospectively enrolled in our study. Machine learning methods, including recursive feature elimination (RFE), the synthetic minority oversampling technique (SMOTE), and the support vector machine (SVM) classifier, were used to construct models based on clinical-pathological factors (clinical model), radiomic features from RS-EPI DWI (radiomics model), and their combination (merged model). The Harrell concordance index (C-index) and the area under the time-dependent receiver operating characteristic curve (AUC) were calculated to evaluate the predictive performance at 1 year, 3 years, and 5 years. Kaplan‒Meier analysis was performed to evaluate the ability to stratify patients according to the risk of ROM. Findings The merged model performed well in predicting tumour ROM in patients with RC at 1 year, 3 years, and 5 years in both cohorts (AUC = 0.887/0.813/0.794; 0.819/0.795/0.783) and was significantly superior to the clinical model (AUC = 0.87 [95% CI: 0.80–0.93] vs. 0.71 [95% CI: 0.59–0.81], p = 0.009; C-index = 0.83 [95% CI: 0.76–0.90] vs. 0.68 [95% CI: 0.56–0.79], p = 0.002). It also had a significant ability to differentiate patients with a high and low risk of ROM (HR = 12.189 [95% CI: 4.976–29.853], p < 0.001; HR = 6.427 [95% CI: 2.265–13.036], p = 0.002). Conclusion Our developed merged model based on RS-EPI DWI accurately predicted and effectively stratified patients with RC according to the ROM risk at an early stage with an individualized profile, which may be able to assist physicians in individualizing the treatment protocols and promote a meaningful paradigm shift in RC treatment from traditional reactive medicine to PPPM.

RETRACTED ARTICLE: RINT1 is a new suppression target to reduce colon cancer cell growth, migration and invasion through regulating ZW10/NAG-1 expression - Jinheng Xu; Meng Zhao; Shunxian Huang; Qian Wu; Minghe Bai; Xueli Zhao; Jixian Wang; Yueming Hu; Junwei Feng; Zhiyong Zhang (Molecular and Cellular Biochemistry, 2022)

Simulation and risk assessment of typical antibiotics in the multi-media environment of the Yangtze River Estuary under tidal effect - Chaomeng Dai; Yueming Han; Yan Li; Yanping Duan; Shuguang Liu; Yalei Zhang; Yaojen Tu (Environmental Science and Pollution Research, 2022)

Consequences of Coastal Wetlands Reclamation and the Need for Integrating Impact Assessment of Invasive Alien Plants Species and Coastal Armoring in Life Cycle Assessment (LCA) - Taitiya Kenneth Yuguda; Zhanrui Leng; Yueming Wu; Hui Jia; Sai Zhang; Zhicong Dai; Jian Li; Daolin Du (International Journal of Environmental Research, 2022)

The IAMAS-CNC Early Career Scientists Nobel Prize Online Interpretation Workshop - Jing Li; Zhongjing Jiang; Yueming Dong; Lu Zhang; Tong Ying; Zhenyu Zhang; Mu Mu (Advances in Atmospheric Sciences, 2022)

Establishment of Galectin-3 Time-resolved Fluoroimmunoassay and its Application in Idiopathic Membranous Nephropathy - Xiaomei Yu; Lingli Chen; Bo Lin; Li Zhang; Xue Yang; Xiaobin Liu; Pengguo Xia; Yueming Liu; Shaoxiong Zheng; Xiumei Zhou; Yigang Wang; Yuan Qin; et al. (Journal of Fluorescence, 2022)

Representativeness and Redundancy-Based Band Selection for Hyperspectral Image Classification` - Yufei Liu; Xiaorun Li; Yueming Feng; Liaoying Zhao; Wenqiang Zhang (International Journal of Remote Sensing, 2021)

Study on calculation and validation of tropospheric ozone by ozone monitoring instrument – microwave limb sounder over China - Yueming Hu; Huanhuan Yan; Xingying Zhang; Yi Gao; Xiangdong Zheng; Xuyan Liu (International Journal of Remote Sensing, 2020)

ATP-binding cassette g1 regulates osteogenesis via Wnt/β-catenin and AMPK signaling pathways - Lei Zhou; Shiwei Sun; Tieqi Zhang; Yueming Yu; Liang Xu; Haoran Li; Minghai Wang; Yang Hong (Molecular Biology Reports, 2020)

Phycocyanin fluorescent probe from Arthrospira platensis: preparation and application in LED-CCD fluorescence density strip qualitative detection system - Yunquan Zheng; Liuda Mo; Wenyi Zhang; Yunjian Duan; Jiandong Huang; Chengqun Chen; Yueming Gao; Xianai Shi; Feng Li; Jianmin Yang; Yanghao Guo (Journal of Applied Phycology, 2019)

Increased associated effects of topography and litter and soil nutrients on soil enzyme activities and microbial biomass along vegetation successions in karst ecosystem, southwestern China - Fujing Pan; Wei Zhang; Yueming Liang; Shujuan Liu; Kelin Wang (Environmental Science and Pollution Research, 2018)

Alterations in the proteome of wheat primary roots after wortmannin application during seed germination - Hui Cao; Xiaolin Ni; Caiyun Zhang; Wenshuo Shi; Yuxing Xu; Yueming Yan; Feixiong Zhang (Acta Physiologiae Plantarum, 2017)

Characterization of re-grown floc size and structure: effect of mixing conditions during floc growth, breakage and re-growth process - Jun Nan; Zhenbei Wang; Meng Yao; Yueming Yang; Xiaofei Zhang (Environmental Science and Pollution Research, 2016)

Molecular cloning and potential function prediction of homologous SOC1 genes in tree peony - Shunli Wang; Margherita Beruto; Jingqi Xue; Fuyong Zhu; Chuanjiao Liu; Yueming Yan; Xiuxin Zhang (Plant Cell Reports, 2015)

Zircon ages and geochemical data of the Biluutiin ovoo ophiolite: implication for the tectonic evolution of South Mongolia - Mingshuai Zhu; Laicheng Miao; Munkhtsengel Baatar; Fochin Zhang; Chimedtseren Anaad; Shunhu Yang; Yueming Li (International Geology Review, 2014)

EOLA1 protects lipopolysaccharide induced IL-6 production and apoptosis by regulation of MT2A in human umbilical vein endothelial cells - Yueming Liu; Hairong Liu; Wenhai Chen; Ting Yang; Wei Zhang (Molecular and Cellular Biochemistry, 2014)

Experimental Research on the In Vitro Antitumor Effects of Crataegus sanguinea - Jianling Sun; Guolan Gao; YuLian Gao; liJuan Xiong; Xiaoying Li; Jihong Guo; Yueming Zhang (Cell Biochemistry and Biophysics, 2013)

Integrating fuzzy logic with piecewise linear regression for detecting vegetation greenness change in the Yukon River Basin, Alaska - Yueju Xue; Shuguang Liu; Li Zhang; Yueming Hu (International Journal of Remote Sensing, 2013)

Retinol-binding protein 4 as a risk factor for cholesterol gallstone formation - Tao Han; Diancai Zhang; Zan Fu; Yueming Sun; Wei Yang; Cuimei Yuan (Molecular and Cellular Biochemistry, 2013)

Overexpression of d-psicose 3-epimerase from Ruminococcus sp. in Escherichia coli and its potential application in d-psicose production - Yueming Zhu; Yan Men; Wei Bai; Xiaobo Li; Lili Zhang; Yuanxia Sun; Yanhe Ma (Biotechnology Letters, 2012)

Phylogenetic relationship of a new class of LMW-GS genes in the M genome of Aegilops comosa - Ke Wang; Liyan Gao; Shunli Wang; Yanzhen Zhang; Xiaohui Li; Miaoyi Zhang; Zhenze Xie; Yueming Yan; Matthew Belgard; Wujun Ma (Theoretical and Applied Genetics, 2011)

Molecular characterization of the celiac disease epitope domains in α-gliadin genes in Aegilops tauschii and hexaploid wheats (Triticum aestivum L.) - Zhenze Xie; Congyan Wang; Ke Wang; Shunli Wang; Xiaohui Li; Zhao Zhang; Wujun Ma; Yueming Yan (Theoretical and Applied Genetics, 2010)

Paleogene-Neogene stratigraphic realm and sedimentary sequence of the Qinghai-Tibet Plateau and their response to uplift of the plateau - KeXin Zhang; GuoCan Wang; JunLiang Ji; ManSheng Luo; XiaoHu Kou; YueMing Wang; YaDong Xu; FenNing Chen; RuiMing Chen; BoWen Song; JianYu Zhang; YinPing Liang (Science China Earth Sciences, 2010)

Overexpression and characterization of a thermostable trehalose synthase from Meiothermus ruber - Yueming Zhu; Dongsheng Wei; Jun Zhang; Yufan Wang; Hengyi Xu; Laijun Xing; Mingchun Li (Extremophiles, 2010)